2009
DOI: 10.2478/s11658-008-0037-2
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin-transferrin conjugate selectively overcomes multidrug resistance in leukaemia cells

Abstract: Neoplastic cells frequently have an increased number of transferrin receptors. Coupling transferrin to an anti-neoplastic drug has the potential to overcome multidrug resistance (MDR). The purpose of this study was to examine the distribution and action of doxorubicin-transferrin conjugate (DOX-TRF) in a leukaemia cell line (HL60), a multidrug-resistant leukaemia cell line (HL60ADR) and a normal tissue cell line (human fibroblasts). The intracellular accumulation of DOX and DOX-TRF was monitored by direct fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…The protein conjugate was shown not to translocate to the nucleus, but to act on various enzymes within the plasma membrane, suggesting that the action of ADR was directed by the physiological interactions of Tf [26, 27, 31]. Importantly, this conjugate was also able to overcome multidrug resistance while minimizing toxicity to normal cells [28, 32, 33]. …”
Section: Targeting Moiety Conjugated Directly To the Active Compoundmentioning
confidence: 99%
“…The protein conjugate was shown not to translocate to the nucleus, but to act on various enzymes within the plasma membrane, suggesting that the action of ADR was directed by the physiological interactions of Tf [26, 27, 31]. Importantly, this conjugate was also able to overcome multidrug resistance while minimizing toxicity to normal cells [28, 32, 33]. …”
Section: Targeting Moiety Conjugated Directly To the Active Compoundmentioning
confidence: 99%
“…The increased cytotoxicity of transferrin-DOX conjugate over that of free DOX was partly explained by the conjugate bio-reductive processes and ROS generation in cytoplasma. The ability of the transferrin-DOX conjugate to overcome MDR was further confirmed by Łubgan, where the conjugate was 4- and 200-fold more cytotoxic than free DOX in sensitive HL-60 and resistant HL-60/ADR leukemia cells, respectively [111]. Interestingly, when Munns et al investigated transferrin-DOX conjugate in sensitive MGH-U1 and resistant MGH-U1R bladder cancer cell lines, it was found that the conjugate did not overcome resistance [112].…”
Section: Anthracycline Nanoparticles To Overcome Mdrmentioning
confidence: 99%
“…Based on the cytotoxicity MTT-Assay, Lubgan et al [24] found that respective DOX and DOX-TRF IC 50 values for HL60 cells were 0.08 μM and 0.02 μM, whereas 7 μM doxorubicin and 0.035 μM DOX-TRF were required to cause 50% growth inhibition in the doxorubicin-resistant cell line. Moreover, studies performed by Fritzer et al proved that in highly multidrug resistant KB-C1 and KB-V1 cells, DOX up to 1 μM did not cause any cytotoxic effects, while the DOX-TRF conjugate inhibited the colony formation of these cells with IC 50 levels of 0.2 and 0.025 μM, respectively [33] As shown in Fig.…”
Section: Page 9 Of 23mentioning
confidence: 98%
“…DOX-TRF conjugate was synthesized and analyzed according to the modified procedure [23,24] presented in our previous work [21]. For carrying out the conjugation procedure, human transferrin, glutaraldehyde and ethanolamine were supplied from Sigma (Darmstadt, Germany).…”
Section: Chemical Compoundsmentioning
confidence: 99%